ALCOHOLIC AND WATERY EXTRACT EFFECT OF EUCALYPTUS IN GERMINATING, GROWTH, AND PRODUCT OF WHEAT (Triticum aestivum L.) TAMOOZ-1 - Jumaa, Najm Abdullah; Abrahim, Nagham Saddon (Diyala Agricultural Sciences Journal, 2011)
The effectiveness of alcoholic and watery extract of Eucalyptus globules in germinating, growth, and yield component of wheat (Tamooz-1) was investigated by two experiments were carried in laboratory and green house of department of biology in education College \ Al-Razi. Seeds of wheat were planted in plats and treated with extraction of (cold water , hot water, and alcohol) with concentration of ( 0 ,0.5 ,1 ,3 ,5% ).The number of treatments were about (15) and with three replications. By this we had (45)treatment plants. While the experiment in green-house including a watering the plants after with same used germination with the same plant ex tract and with same concentration in lab-experiment There were three replications for each treatment . So we had also (45) observations in this experiment. The used concentrations for alcoholic and watery extractions in laboratory experiment showed significant effect in each percentage for germination. Percentage for speed of germination, and the length of both radicle and plumule .it was noticed that significance increase of these aspects occurred When adding extraction with (0.5%) concentrations, it was also noticed that there was frustrating effect for these extraction in the mentioned aspects which is acceptable Expelling with the increase of concentration for these extraction to the amount(5%). . As for the green-house experiment it showed that adding plant extraction with (%3. 1. 0.5) concentration led to significant increase in each of plant height, soft weight of total Greenness dry weight of total greenness , total leaf area index , number of seeds in each Earhead and weight of 100 seeds, this could by followed by abbreviating in the Mentioned aspects when increasing the concentrations of these extractions. The results showed that the extraction method also had its effect on the studied aspects .the extraction method with cold water led to significant increase in percentage for germination, dry Weight and the length of the plumule .also extraction Method with boiling water showed significant increase in percentage for speed of germination ,soft weight of total greenness ,number of branched ,number of earhead ,number of seed in each earhead, leaf area and Weight of 100 seeds. As for extraction method with cold alcoholic significantly effected On each of plant height and length of redicle.